Inhibitory Effect of Extract Granule of Earthworms (Lumbricus rubellus) on the Pathogenic Bacteria In Vitro - Lusty Istiqomah; Ema Damayanti; Hardi Julendra; Dewi istika; Sri Winarsih (Jurnal Sain Veteriner, 2014)
The objective of this study was to determine the inhibition ability of the earthworm (L. rubellus) extract (ECT), dried earthworm extract (ECT-k), and granule earthworm extract (ECT-g) as poultry feed additive against some pathogenic bacteria. Antibacterial activity was performed using diffusion method against Escherichia coli, Salmonella pullorum, Pseudomonas aeruginosa, and Staphylococcus aureus  in vitro. In the present study, the concentrations of ECT, ECT-k, and ECT-g in nutrient broth (NB) media tested were consisted of treatments A: 0%, B: 0.26%, C: 0.52%, D: 0.78% and E: 1.04% (g/vol) respectively. The results of the in vitro study showed that started from ECT level 0.26% inhibited (P <0.05) growth of P. aeruginosa and S. aureus, while ECT level 0.52% inhibited (P <0.05) E. coli and S. pullorum which proportional to the increased in concentration. ECT-k level 0.26% inhibited (P <0.05) growth of E. coli and S. aureus, while ECT-k level 0.52% inhibited (P <0.05) P. aeruginosa, and ECT-k level 1.04% inhibited (P<0.05) growth of S. pullorum. ECT-g level 0.26% inhibited (P <0.05) growth of S. pulorum, while ECT-g level 0.52% inhibited (P <0.05) S. aureus and ECT-g level 1.04% inhibited (P<0.05) growth of P. aeruginosa. There were no antibacterial action (P>0.05) of ECT and ECT-t against S. pullorum. Diameter of inhibition zone for 24 hours showed that S. aureus was the most sensitive bacterium to ECT and ECT-k, and S. pullorum was the most sensitive bacterium to ECT-g.